Anti‐Oxidizing Radical Polymer‐Incorporated Perovskite Layers and their Photovoltaic Characteristics in Solar Cells. Issue 23 (30th October 2019) - Suwa, Koki; Oyaizu, Kenichi; Segawa, Hiroshi; Nishide, Hiroyuki
Abstract: A small amount of a radical‐bearing redox‐active polymer, poly(1‐oxy‐2, 2, 6, 6‐tetramethylpiperidin‐4‐yl methacrylate) (PTMA), incorporated into the photovoltaic organo‐lead halide perovskite layer significantly enhanced durability of both the perovskite layer and its solar cell and even exposure to ambient air or oxygen. PTMA acted as an eliminating agent of the superoxide anion radical formed upon light irradiation on the layer, which can react with the perovskite compound and decompose it to lead halide. A cell fabricated with a PTMA‐incorporated perovskite layer and a hole‐transporting polytriarylamine layer gave a photovoltaic conversion efficiency of 18.8 % (18.2 % for the control without PTMA). The photovoltaic current was not reduced in the presence of PTMA in the perovskite layer probably owing to a carrier conductivity of PTMA. The incorporated PTMA also worked as a water‐repelling coating for providing humidity‐resistance to the organo‐lead halide perovskite layer. Abstract : Radically super : A radical‐bearing redox‐active polymer, poly(1‐oxy‐2, 2, 6, 6‐tetramethylpiperidin‐4‐yl methacrylate) (PTMA), significantly enhances the durability of an organo‐lead halide perovskite layer in a solar cell without decreasing the photovoltaic conversion performance. PTMA could work both as an eliminating agent of superoxide anion radical and as a carrier mediator in the perovskite under irradiation.